Developing cross‐specialty endovascular simulation training. (October 2014) - Nelson, Katharine; Bagnall, Alan; Nesbitt, Craig; Davey, Philip; Mafeld, Sebastian
Summary Background Simulation is increasingly recognised as a valuable tool in training tomorrow's doctors. This technology has the potential to improve patient safety and address some of the challenges posed by recent changes in doctors' training, yet the uptake has been slow in the majority of institutions. In our own centre, we noted existing equipment was used infrequently. We sought to address this problem through the development of a 1–day training course in simulation (SIM) and basic interventional skills aimed at trainees from across different endovascular specialties. Methods A 1–day course for trainees in cardiology, interventional radiology and vascular surgery was piloted. A variety of endovascular simulators were used to teach core skills common to all three specialties, under the umbrella theme of safe access, safe navigation and safe closure. Independent continuing use of SIM‐based training was encouraged. Trainee and faculty member experiences of SIM training in a cross‐specialty environment were explored by interview and online questionnaire. Results Thirty‐six trainees completed the pilot training course. Feedback was almost universally positive, with all trainees agreeing that SIM was useful in achieving the course's objectives, and that they would recommend the course to a colleague. Cross‐specialty training was viewed positively by trainees and trainers alike, with benefits identified in knowledge and skills sharing, as well as fostering better clinical collaboration. SIM‐based training was perceived as useful in promoting patient safety, and is considered to be a desirable component of future training. Discussion We present a SIM‐based model that achieves economies of scale by delivering common skill‐set training for doctors from different specialties. Through our experiences piloting this course we discuss how the recognised barriers to adopting this new technology may be addressed and offer insights into how SIM may be integrated into existing training programmes.